A SLAF-based high-density genetic map construction and genetic architecture of thermotolerant traits in maize (Zea mays L.) - Wen, Tingting; Zhang, Xuefei; Zhu, Jiaojiao; Zhang, Susu; Rhaman, Mohammad Saidur; Zeng, Wei (Frontiers in Plant Science, 2024)
The leaf scorching trait at flowering is a crucial thermosensitive phenotype in maize under high temperature stress (HS), yet the genetic basis of this trait remains poorly understood. In this study, we genotyped a 254 RIL-F2:8 population, derived from the leaf scorch-free parental inbred line Abe2 and the leaf scorching maternal inbred line B73, using the specific-locus amplified fragment sequencing (SLAF-seq) method. A total of 10,112 polymorphic SLAF markers were developed, and a high-density genetic map with a total length of 1,475.88 cM was constructed. The average sequencing depth of the parents was 55.23X, and that of the progeny was 12.53X. Then, we identified a total of 16 QTLs associated with thermotolerant traits at flowering, of which four QTLs of leaf scorching damage (LS) were distributed on chromosomes 1 (qLS1), 2 (qLS2.1, qLS2.2) and 3 (qLS3), which could explain 19.73% of phenotypic variation. Combining one qLS1 locus with QTL-seq results led to the identification of 6 candidate genes. Expression experiments and sequence variation indicated that Zm00001d033328, encoding N-acetyl-gamma-glutamyl-phosphate reductase, was the most likely candidate gene controlling thermotolerant traits at flowering. In summary, the highdensity genetic map and genetic basis of thermotolerant traits lay a critical foundation for mapping other complex traits and identifying the genes associated with thermotolerant traits in maize.